Comparison of perfusion models for quantitative T1 weighted DCE-MRI of rectal cancer [dataset] - Uhrig, Tanja; Neumann, Wiebke; Janssen, Sonja; Attenberger, Ulrike; Schönberg, Stefan; Schad, Lothar R.; Zöllner, Frank G. (Universität, 2017)
Twenty-six patients with newly diagnosed rectal carcinoma underwent 3T MRI of the pelvis including a T1 weighted dynamic contrast enhanced (DCE) protocol before treatment. For eighteen patients, mean values for Plasma Flow (PF), Plasma Volume (PV) and Mean Transit Time (MTT) were obtained for three perfusion models.